Barley root traits for improved subsoil exploration and resource capture - Heras Ambros, Paloma (2017)
Subsoil physical characteristics are often limiting to root growth, one of the major reasons being high density soil. However, deeper and more efficient root systems could help to explore a larger soil volume and reduce the input of nitrogen fertilisers if roots make more use of the nitrogen at depth. The first target was to develop a screening method which allowed barley root extension rates to be quantified after four days of growth in loose and compacted soils. Firstly, seed quality (loss of germination ability caused by poor conditions in storage and long storage time) was identified as a potential source of variation for root extension rate in seedlings. The screening showed that roots growing in compacted soil had a slower extension rate than roots growing in loose soil. In addition, there was an interaction between soil conditions and cultivars meaning that not all of them showed the same ability to overcome high soil density. Root architecture was characterized at days eight and 12 after planting for four selected divergent cultivars. Measurements were made using X-ray micro-computed tomography (µCT)-scanning. The differences between the four genotypes in root architecture (number of primary roots, root extension rate, root length, root area, root volume, convex hull, centre of mass, lateral density, lateral length) were significant at eight days after planting but disappeared at 12 days after planting for most of the traits measured (i.e. growth rate of primary roots). Soil density influenced the root system architecture at both two-time points, roots elongated less and explored less soil in the high compaction treatment. A third experiment was conducted to test the hypothesis that the differences in root architecture observed between the genotypes in response to the soil bulk density in the µCT-scanning would lead to different patterns of nutrient uptake from topsoil and subsoil. Layered soil columns of topsoil and subsoil were constructed with different subsoil physical parameters (loose, compacted and compacted with macropores) and a nitrogen tracer to measure nitrogen capture from the subsoil. Root length density and other traits determining root architecture differed between two barley cultivars and oat, but increased root length density in the subsoil did not improve nitrogen uptake from the subsoil. Hence showing that nitrogen uptake from the subsoil was not directly related with a greater presence of roots in the experiment.